Spatial and Temporal Analysis of Ecological Footprint and Ecological Carrying Capacity of Water Resources in Guangzhou - ZHAO Zixi (Renmin Zhujiang)
In order to quantitatively analyze the pressure of regional water resources and evaluate the status of sustainable development of water resources.Based on the ecological footprint model of water resources,this paper analyzes the temporal and spatial differences of ecological footprint and ecological carrying capacity in Guangzhou from 2005 to 2019.The results show that the per capita ecological footprint of water resources in Guangzhou is decreasing year by year,the per capita water resources carrying capacity is consistent with the total amount of water resources,and the fluctuation is large.The water resources are in surplus,and the ecological footprint of water resources per 10 000 yuan GDP is decreasing year by year.The water resources account of Guangzhou is in a safe state.The regions with larger ecological footprint of water resources per capita are located in Huangpu and Nansha District,while those in Baiyun,Tianhe and Haizhu District are smaller.The distribution of per capita water resources carrying capacity of each district is:Conghua District>Zengcheng District>Huadu District>Nansha District>Huangpu District>Panyu District>Central District.According to the analysis results,it is suggested that the administrative regions of Guangzhou should upgrade their industries according to the government planning and the actual distribution and utilization of water resources,so as to improve the water use efficiency and realize the sustainable utilization of water resources.